Increased Frequency of Indels in Hypervariable Regions of SARS-CoV-2 Proteins—A Possible Signature of Adaptive Selection - Alisoltani, Arghavan; Jaroszewski, Lukasz; Iyer, Mallika; Iranzadeh, Arash; Godzik, Adam (Frontiers in Genetics, 2022)
Most attention in the surveillance of evolving SARS-CoV-2 response to vaccinations and survival immunity has been centered on nucleotide substitutions in the spike glycoprotein. We show that in-frame insertions and deletions (indels) play a significant and rapidly increasing role in the evolution of the SARS-CoV-2 genome, including its immune signature. The percentage of genomes and lineages with indels is increasing rapidly, especially in all variants of concern (VOCs). Monitoring of SARS-CoV-2 genome evolution uncovers that co-occurrence (i.e., highly correlated presence) of indels, especially deletions on spike N-terminal domain and non-structural protein 6 (NSP6) is a shared feature in several VOCs such as Alpha, Beta, Delta, and Omicron. These appear to affect interactions with the host immune components more dramatically than substitutions. Indels distribution is correlated with spike mutations associated with immune escape and growth in the number of genomes with indels coincides with the increasing population resistance due to vaccination and previous infections. Indels occur most frequently in the spike, but also in other proteins, especially those involved in interactions with the host immune system. We also showed that indels concentrated on specific regions of individual SARS-CoV-2 proteins known as hypervariable regions (HVRs) which are mostly located in protein loop regions. Structural analysis suggests that indels remodel viral proteins’ surfaces at common epitopes and interaction interfaces, affecting the virus’ interactions with host proteins. We hypothesize that the increased frequency of indels, the non-random distribution of them and their independent co-occurrence in several VOCs from diverse geographic origins (i.e., repeated appearance of the same combinations of indels) is an adaptive response to elevated global population immunity.